Thromboelastography Parameter and Its Association with Survival of COVID-19 Patients: A Retrospective Cross-Sectional Study - Hernaningsih, Yetti; Wiyono, Nita; Hajat, Arifoel; Notopuro, Paulus Budiono; Mohd Yusoff, Narazah; Moses, Emmanuel Jairaj (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Coagulopathy associated with Coronavirus disease 2019 (COVID-19) may cause life-threatening complications, especially in severe or critically ill COVID-19 patients. Thromboelastography (TEG) is an effective, dynamic, and reliable test to assess the complete coagulation process. This study aimed to determine the association between selected TEG parameters and survival in COVID-19 patients. Methods: This study was a retrospective observational study using data from medical records of COVID-19 patients who were hospitalized in Dr. Soetomo Hospital, Surabaya, Indonesia. There were 94 COVID-19 patients consisting of 76 survivors and 18 non-survivors. The association between TEG results and certain TEG parameters with survival status was considered significant if the p-value ≤ 0.05. Result: Increased coagulation activity had a significant association with the survival status of COVID-19 patients (p=0.04). There were no significant differences in all TEG parameters between COVID-19 patients who survived and those who did not survive (p > 0.05). Based on the TEG analysis tree, the most TEG results found were secondary fibrinolysis (21.3%) and fibrinolytic shutdown (24.5%). No significant association was found between the coagulability and fibrinolysis abnormality with the survival status in COVID-19 patients (p > 0.05). Conclusion: There was no significant difference in TEG results between COVID-19 survivors and non-survivors. However, based on the TEG result, an increase in coagulation activity is associated with a lower survival rate. Further study with detailed timing of TEG examination, disease severity and comorbidities stratification in COVID-19 patients may be neededs. REFERENCES Neethling C, Calligaro G, Miller M, Opie JJS. The evolution of clot strength in critically-ill COVID-19 patients : a prospective observational thromboelastography study. Thromb J. 2021;19(83):1–11. doi: 10.1186/s12959-021-00331-5. [Google Scholar] [PMC free article] [Pubmed] Sehgal T, Aggarwal DMM, Baitha DMU, Gupta G, Prakash B, Gupta A, et al. Thromboelastography determined dynamics of blood coagulation and its correlation with complications and outcomes in patients with coronavirus disease 2019. Res Pr Thromb Haemost. 2022;6(1):1–10. doi: 10.1002/rth2.12645. eCollection 2022 Jan.[<a href="https://scholar.google.com/scholar_lookup?title=Thromboelastography+determined+dynamics+of+blood+coagulation+and+its+correlation+with+complications+and+outcomes+in+patients+with+coronavirus+disease+2019&btnG=">Google Scholar] [PMC free article] [Pubmed][Crossref] Cordier P, Noel A, Martin E, Contargyris C. Complex and prolonged hypercoagulability in coronavirus disease 2019 intensive care unit patients: A thromboelastographic study. Aust Crit Care. 2021;34:160–6. doi: 10.1016/j.aucc.2020.11.007. [Google Scholar] [PMC free article] [Pubmed][Crossref] Hartmann J, Ergang A, Mason D, Dias JD. The Role of TEG Analysis in Patients with COVID-19-Associated Coagulopathy : A Systematic Review. Diagnostics. 2021;11(172):1–13. doi: 10.3390/diagnostics11020172. [Google Scholar] [PMC free article] [Pubmed] Dumilah HD, Kahar H, Hajat A, Setiawan P, Soebroto H. TEG’s Utility to Detect Hypercoagulability in Adult Patients at Post-Cardiac Surgery Using Cardiopulmonary Bypass in ICU. Indones J Clin Pathol Med Lab. 2020;27(1):90–6. doi: 10.1177/10760296211047231. [Google Scholar] Xuan J, Wang J, Wei B. Diagnostic Value of Thromboelastography (TEG) for the Diagnosis of Death in Infected Patients. Crit Appl Thromb. 2021;27(5):1–11. doi:10.1177/10760296211047231.[Google Scholar] [PMC free article] [Pubmed] Sankaravadivoo P. Thromboelastography–A Review. Res J Pharm Technol. 2018;11(3):1225–7. doi: 10.5958/0974-360X.2018.00227.5 [Google Scholar] Shaydakov ME, Sigmon DF, Blebea J, Bhargava J, Hurley JA. Thromboelastography. StatPearls Publ. 2022;1–8.[Pubmed] Yuriditsky E, Horowitz JM, Merchan C, Ahuja T, Brosnahan SB, McVoy L, et al. Thromboelastography Profiles of Critically Ill Patients with Coronavirus Disease 2019. Crit Care Med. 2020;1319–26. doi: 10.1097/CCM.0000000000004471. [Google Scholar] [PMC free article] [Pubmed] Hernaningsih Y, Aryati, Notopuro PB, Hajat A., et al. Aspek Laboratorium COVID-19. Surabaya: Airlangga University Press; 2021. [Google Scholar] Abou-ismail MY, Diamond A, Kapoor S, Arafah Y. The hypercoagulable state in COVID-19: Incidence, pathophysiology, and management. Thromb Res. 2020;194:101–15. doi: 10.1016/j.thromres.2020.06.029.[Google Scholar][Pubmed][Crossref] Acherjee T, Behara A, Saad M, Vittorio TJ. Mechanisms and management of prothrombotic state in COVID-19 disease. Ther Adv Cardiovasc Dis. 2021;15:1–13. doi: 10.1177/17539447211053470. [Google Scholar][Pubmed] Schulman S, Hu Y, Konstantinides S. Venous thromboembolism in children. Thromb Haemost. 2020;120(12):1642–53. doi: 10.1055/s-0040-1718532. [Google Scholar] Singhania N, Bansal S, Nimmatoori DP, Ejaz AA, Mccullough PA. Current Overview on Hypercoagulability in COVID - 19. Am J Cardiovasc Drugs [Internet]. 2020;20(5):393–403. doi:10.1007/s40256-020-00431-z [Google Scholar][Pubmed] Panigada M, Bottino N, Tagliabue P, Grasselli G, Novembrino C, Chantarangkul V, et al. Hypercoagulability of COVID-19 patients in intensive care unit : A report of thromboelastography findings and other parameters of hemostasis. 2020;(April):1738–42. doi: 10.1111/jth.14850. Epub 2020 Jun 24.[<a href="https://scholar.google.com/scholar_lookup?title=Hypercoagulability+of+COVID-19+patients+in+intensive+care+unit%E2%80%AF%3A+A+report+of+thromboelastography+findings+and+other+parameters+of+hemostasis&btnG=">Google Scholar][Pubmed][Crossref] Mortus JR, Manek SE, Brubaker LS, Loor M, Cruz MA, Trautner BW, et al. Thromboelastographic Results and Hypercoagulability Syndrome in Patients With Coronavirus Disease 2019 Who Are Critically Ill. JAMA Infect Dis. 2020;3(6):2020–3. doi: 10.1001/jamanetworkopen.2020.11192. [<a href="https://scholar.google.com/scholar?hl=en&as_sdt=0%2C5&q=Mortus+JR%2C+Manek+SE%2C+Brubaker+LS%2C+Loor+M%2C+Cruz+MA%2C+Trautner+BW%2C+et+al.+Thromboelastographic+Results+and+Hypercoagulability+Syndrome+in+Patients+With+Coronavirus+Disease+2019+Who+Are+Critically+Ill&btnG=">Google Scholar] [PMC free article] [Pubmed][Crossref] Bocci MG, Maviglia R, Consalvo LM, Grieco DL, Montini L, Mercurio G, et al. Thromboelastography clot strength profiles and effect of systemic anticoagulation in COVID-19 acute respiratory distress syndrome: A prospective, observational study. Eur Rev Med Pharmacol Sci. 2020;24(23):12466–79. doi: 10.26355/eurrev_202012_24043. [<a href="https://scholar.google.com/scholar_lookup?title=Thromboelastography+clot+strength+profiles+and+effect+of+systemic+anticoagulation+in+COVID-19+acute+respiratory+distress+syndrome%3A+A+prospective%2C+observational+study&btnG=">Google Scholar][Pubmed] Wright FL, Vogler TO, Moore EE, Moore HB, Wohlauer M V., Urban S, et al. Fibrinolysis Shutdown Correlation with Thromboembolic Events in Severe COVID-19 Infection. J Am Coll Surg [Internet]. 2020;231(2):193-203.e1. doi: 10.1016/j.jamcollsurg.2020.05.007 [Google Scholar] [PMC free article] [Pubmed][Crossref] Blydenstein SA Van, Menezes CN, Miller N, Johnson N, Pillay B, Jacobson BF, et al. Prevalence and Trajectory of COVID-19-Associated Hypercoagulability Using Serial Thromboelastography in a South African Population. Crit Care Res Pract. 2021;(3935098):1–9. doi: 10.1155/2021/3935098. eCollection 2021.[Google Scholar][Pubmed] Salem N, Atallah B, El Nekidy WS, Sadik ZG, Park WM, Mallat J. Thromboelastography findings in critically ill COVID-19 patients. J Thromb Thrombolysis [Internet]. 2021;51(4):961–5. doi:10.1007/s11239-020-02300-7.[Google Scholar][PMC free article] [Pubmed] Marvi TK, Stubblefield WB, Tillman BF, Tenforde MW, Patel MM, Lindsell CJ, et al. Serial Thromboelastography and the Development of Venous Thromboembolism in Critically Ill Patients With COVID-19. Crit Care Explor. 2022;4(1):e0618. doi: 10.1097/CCE.0000000000000618. eCollection 2022 Jan. [Google Scholar][PMC free article] [Pubmed] Stillson JE, Bunch CM, Gillespie L, Khan R, Wierman M, Pulvirenti J, et al. Thromboelastography-Guided Management of Anticoagulated COVID-19 Patients to Prevent Hemorrhage. Semin Thromb Hemost. 2021;47(4):442–6. doi: 10.1055/s-0041-1723754. Epub 2021 Feb 19. [<a style="background-color: #ffffff; font-size: 0.875rem;" href="https://scholar.google.com/scholar_lookup?title=Thromboelastography-Guided+Management+of+Anticoagulated+COVID-19+Patients+to+Prevent+Hemorrhage&btnG=">Google Scholar][Pubmed]